Approaches for assessing decision-making capacity in older adults: a scoping review protocol. Issue 4 (April 2020) - Usher, Ruth; Stapleton, Tadhg
ABSTRACT: Objective: This review will identify and map existing evidence on current approaches to determining decision-making capacity in older adults. It will provide a summary of available evidence and policies and identify gaps in research. Introduction: Assessment of decision-making capacity is emerging as an important issue in society and healthcare. It is considered an ethically challenging area of clinical practice, and issues with implementation have been identified internationally. With the aging population increasing globally, approaches to assess and support decision-making are becoming more pertinent. Inclusion criteria: This scoping review will consider studies on assessment approaches and procedures that are used to evaluate the decision-making capacity of older adults, aged 60 years and over. It will include those with age-related cognitive impairment, dementia, and neurodegenerative conditions. Quantitative, qualitative, and mixed-methods studies along with gray literature, including expert opinions, policies reports, and practice guides, will be included. Methods: The JBI scoping review methodological framework will be used. The review will also be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist for scoping reviews. The following major healthcare databases will be searched: MEDLINE, PsycINFO, Embase, CINAHL, Cochrane Databases, Web of Science, and Scopus. The search will cover studies published in English from January 2000 to the present date. Titles and abstracts will be screened against inclusion criteria. Data will be extracted using a form developed for this review. A stakeholder consultation meeting will be held to provide feedback on the findings.